2023
DOI: 10.1097/qad.0000000000003494
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of long-acting injectable cabotegravir as preexposure prophylaxis to prevent HIV acquisition

Abstract: Objective: HIV remains a significant burden, despite expanding HIV prevention tools. Long-acting injectable cabotegravir (CAB-LA) is a new preexposure prophylaxis (PrEP) product. We reviewed existing evidence to determine the efficacy and safety of CAB-LA as PrEP to inform global guidelines. Design: Systematic review and meta-analysis. Methods: We systematically reviewed electronic databases and conference abstracts for citations on CAB-LA from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…A protocol was reviewed by the WHO and prospectively registered in PROSPERO (CRD42021285299). Database searches and article screening were conducted concurrently with a review on safety and efficacy of CAB‐LA as PrEP (CRD42021290713) [22]. Results are reported separately.…”
Section: Methodsmentioning
confidence: 99%
“…A protocol was reviewed by the WHO and prospectively registered in PROSPERO (CRD42021285299). Database searches and article screening were conducted concurrently with a review on safety and efficacy of CAB‐LA as PrEP (CRD42021290713) [22]. Results are reported separately.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents in this and other studies were concerned about potential side effects 12 39. The present analysis showed that pain at the injection site and the potential for rash were rated worse than a potential headache from LA-PrEP.…”
Section: Discussionmentioning
confidence: 61%
“…Together, these studies suggest high proportions of MSM in disparate settings are interested in LA-PrEP; however, these are hypothetical willingness studies, and real-world studies are needed. The logistical challenges of service delivery, uptake and adherence remain 12. Real-world choice and effectiveness should be monitored and evaluated to understand the impact of LA-PrEP on HIV prevention alongside DO PrEP as well as other prevention measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations